Burnout as a Mediator of Quiet Quitting and Employee Well-Being in Generation Z - Bella Pratiwi; Aufizzahra As Syafiyah; Syarifatul Hidni Rafli; Tuti Rahmi (Da'wa Faculty of Islamic State University Salatiga, 2026)
The increasing prevalence of quiet quitting among Generation Z employees has raised concerns regarding its implications for employee well-being and psychological health in the workplace. This study examines the relationship between quiet quitting and employee well-being, with burnout positioned as a mediating variable among Generation Z employees working at a Honda-affiliated company in Padang City, Indonesia. A quantitative correlational design was employed, involving 100 respondents selected through purposive sampling. Data were collected using standardized self-report questionnaires and analyzed using descriptive statistics, Pearson correlation analysis, and mediation analysis through path modeling. The results indicate that quiet quitting is positively associated with burnout and negatively associated with employee well-being. Further analysis reveals that quiet quitting has a significant direct negative effect on employee well-being, as well as an indirect effect through increased levels of burnout, indicating partial mediation. The proposed model explains 5.6% of the variance in burnout and 23.2% of the variance in employee well-being, confirm that disengagement behaviors contribute meaningfully, though not exclusively, to employees’ psychological outcomes. Overall, the findings confirm that quiet quitting represents maladaptive disengagement rather than a protective coping strategy, as it is linked to emotional exhaustion and reduced workplace well-being. These results highlight the importance of organizational interventions aimed at reducing burnout and fostering healthy engagement to support the psychological well-being of young employees and promote sustainable work environments.